The Effect of Food Security and Employment Opportunity on Household Welfare of Farmers in Province of Aceh - Srinita, Srinita (Program Pascasarjana, Universitas Riau, 2016)
Food security is an absolute requirement for the implementation of national development. Food security of the people in the Province of Aceh decreased rapidly because of share expenditure of the people on food. Food security still encounters many heavy obstacles, in the dimension of availability, accessibility, and utilization of food. Food security is not only associated with food, but more strategically it is associated with the fulfillment of quality of the nutrition and protein needed for human resource development, the determinant of future competitiveness of the Indonesian nation in order to improve employment and welfare. The finding of this research shows that food security and employment opportunity partially and simultaneously have significant effect on the household welfare of farmers in Province of Aceh.